Characterisation and undrained strength of amorphous clay - O'Kelly, Brendan (My University, 2014)
This paper presents the physiochemical properties and relationship of saturated remoulded undrained shear strength, sur, against water content, w, for an amorphous organic clay, namely an alum water-treatment residue material derived from the production of potable water. The log w?log sur relationship was found to be strongly linear, and extended well beyond the measured plastic range. The effects of microstructure, and the shearing modes, rates and specimen confinement, are reported, along with the correspondence between sur measured in triaxial compression and that deduced from fall-cone and miniature vane tests. The mobilised strength exhibited high strain-rate dependence, increasing by 30%/log _ cycle increase. The bulk water-treatment residue material could be easily remoulded at water contents below the measured Casagrande plastic limit, indicating that the reported plastic range was notional and, furthermore, that the use of liquidity index as an indicator of the material?s consistency is unreliable. The paper concludes by presenting a conceptual model that goes towards explaining the relatively high values of sur mobilised for this material at extremely high water contents.
PUBLISHED
Keywords: amorphous clay